The effects of cycling using lower limb active passive trainers in people with neurological conditions: a systematic review. (2nd June 2022) - Barclay, Alison; Gray, Stuart R; Paul, Lorna; Rooney, Scott
Abstract : Background Active passive trainers are frequently used as a safe, feasible way for people with neurological disabilities to exercise. However, evidence regarding their efficacy is limited. The aim of this study was to review the literature investigating the effects of lower limb active passive trainer cycling, with or without functional electrical stimulation, on spasticity, cardiovascular fitness, function and quality of life in people with neurological conditions Methods Five electronic databases were searched from inception to June 2021. Studies included: randomised controlled trials using lower limb active passive trainers as a cycling intervention; participants with neurological conditions, such as multiple sclerosis, spinal cord injury, stroke and Parkinson's disease; and at least one outcome related to spasticity, cardiovascular fitness, physical function or quality of life. Results A total of 12 articles were included ( n =423 participants, 52% male). Of these, six used functional electrical stimulation-assisted active passive trainer interventions, and the remaining six used active passive trainer interventions alone. A meta-analysis demonstrated statistically significant improvement in walking endurance; however, this only included stroke studies (6-Minute Walk Test performance, P<0.00001). No statistically significant improvement in walking speed was found ( P =0.31). A significant improvement in spasticity was reported by three studies (two using the active passive trainer intervention alone, one using the active passive trainer with functional electrical stimulation). One study reported improvement in quality of life. Few studies considered cardiovascular fitness. Conclusions The included studies featured heterogeneous designs, outcome measures, exercise prescriptions and participant disability levels, which made comparison difficult. Active passive trainer interventions appear to improve walking endurance in people with stroke; however, the effect on other outcomes and in other conditions remains unclear. It also remains uncertain as to whether functional electrical stimulation-assisted cycling is more beneficial than active passive trainer cycling alone.